Lipid profile in the aqueous humor of diabetic macular edema patients - Mengru Su; Mengru Su; Qinglu Song; Ruiwen Cheng; Ye Zhang; Xinghong Sun; Xinghong Sun; Feng Jiang; Qinghuai Liu (Frontiers in Medicine, 2025)
Diabetic macular edema (DME) has become a global public health focus due to its increasing prevalence and significant impact on central vision. The aim of this study is to analyze the lipid profile characteristics of aqueous humor in DME patients and to identify differential lipid compounds that may serve as potential biomarkers for the pathogenesis and therapeutic intervention. A non-targeted lipidomics approach based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) was used to analyze the lipid profiles of aqueous humor from patients with diabetic macular edema (DME group, 11 cases), diabetic cataracts (DC group, 14 cases), and age-related cataract (ARC group, 15 cases). The validation of identified lipid compounds through Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) was conducted to examine possible varied lipid markers, setting the parameters of VIP > 1 and p < 0.05. Additionally, correlation network analysis, community classification, and functional enrichment analysis were performed on the differential lipids. 90 lipid compounds were identified, encompassing a range of 13 lipid categories. There were significant differences in the lipid profiles of the aqueous humor in DME. The lipid profile characteristics of aqueous humor in patients with DME are described for the first time. Compared to the control group. Various lipid metabolic disorders, such as sphingolipids particularly ceramide, phospholipids, and triglycerides, are involved in the pathogenesis of DME, and can be further studied as potential diagnostic and therapeutic lipid biomarkers.